2017
DOI: 10.1002/ejhf.1077
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of left ventricular systolic dysfunction in pre‐dialysis and dialysis patients with preserved left ventricular ejection fraction

Abstract: The prevalence of impaired LV GLS despite preserved LVEF in pre-dialysis and dialysis patients is relatively high. Patients with preserved LVEF but impaired LV GLS have an increased risk of HF hospitalization and all-cause mortality.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
39
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 23 publications
7
39
1
1
Order By: Relevance
“…In the present research, GLS was lower in the CKD patient group than in the control group, although no significant difference was determined between the groups in terms of GCS. The majority of previous studies have involved stage 3-5 CKD, and significant decreases in both GLS and GCS have been shown, particularly toward the final stage [3,21,22]. The median GFR in the present study was approx-imately 43 mL/min/1.73 m 2 , and our patients had predominantly stage 3 CKD.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…In the present research, GLS was lower in the CKD patient group than in the control group, although no significant difference was determined between the groups in terms of GCS. The majority of previous studies have involved stage 3-5 CKD, and significant decreases in both GLS and GCS have been shown, particularly toward the final stage [3,21,22]. The median GFR in the present study was approx-imately 43 mL/min/1.73 m 2 , and our patients had predominantly stage 3 CKD.…”
Section: Discussionsupporting
confidence: 49%
“…Longitudinal and circumferential fiber deformation can be assessed using STE [20]. Hensen et al [21] investigated EF in normal patients with stage 3-5 end-stage renal failure and revealed decreased GLS in this patient group, which they associated with a higher risk of heart failure-related hospitalization and mortality. Numerous similar studies have shown preserved EF in CKD and decreased GLS associated with hospitalization and cardiovascular mortality [3].…”
Section: Discussionmentioning
confidence: 99%
“…The GLS is measured on the basis of the LV longitudinal shortening in systole, and it is an index of systolic function . It may become abnormal at an earlier stage before a decrease in LVEF . GLS has an independent prognostic value in the mid‐range and preserved LVEF group, because of the loss of prognostic value of LVEF in this HF population .…”
Section: Left Ventricular Ejection Fraction Based Classification: Oppmentioning
confidence: 99%
“…They include an impairment of the cardiac output and of the skeletal muscle diffusion of oxygen during exercise with a different contribution in each patient with HFpEF. [132][133][134] They may influence exercise capacity and limit the value of cardiopulmonary exercise testing or the 6-min walk test distance for the assessment of the patients with HFpEF. 130 Pulmonary mechanisms leading to an increase in the lung dead space have also been shown.…”
Section: Diagnosis and Prognosis: Role Of Exercise Testing And Cardiamentioning
confidence: 99%
“…131 Cardiac and extracardiac comorbidities have a major role in patients with HFpEF. [132][133][134] They may influence exercise capacity and limit the value of cardiopulmonary exercise testing or the 6-min walk test distance for the assessment of the patients with HFpEF. [135][136][137][138] A flattening oxygen consumption trajectory during exercise has been recently introduced as a new measurement of disease severity and a prognostic determinant and its value was independent from LVEF in a first study.…”
Section: Hf With Preserved Ef Diagnosis and Prognosis: Role Of Exercimentioning
confidence: 99%